Factors Associated With The Incidence of Hypertension Among Informal Sector Workers in The Working Area of Darussalam Public Health Center, 2025 - Jelita Marfentin Sari Zendrato; Yolanda E. Br. Ginting; Santy Deasy Siregar; Hartono Hartono; Riky Suherman Simanjuntak (Jurnal Ners, 2026)
Abstract Hypertension is one of the non-communicable diseases that has become a major public health problem because it increases the risk of cardiovascular diseases and premature death. Informal sector workers have diverse job characteristics with varying levels of activity and working conditions that may increase the risk of hypertension. This study aimed to analyze the relationship between several risk factors and the incidence of hypertension among informal sector workers in the working area of Darussalam Public Health Center in 2025. This study used a quantitative research design with a cross-sectional approach. The population consisted of all informal sector workers in the working area of Darussalam Public Health Center, with a total sample of 60 respondents selected using the total sampling technique. Data were collected through questionnaires and blood pressure measurements. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test at a 95% confidence level (Ethical approval number: 048/SP/UNPRI.FI.9.E/SPPKI.1/VIII/2025). The results showed that there was no significant relationship between family history (p=0.113), age (p=0.362), gender (p=0.957), salt consumption (p=0.282), caffeine consumption (p=0.297), physical activity (p=0.241), obesity (p=0.258), work stress (p=0.251), type of occupation (p=0.405), working duration (p=0.492), and income (p=0.100) with the incidence of hypertension. However, there was a significant relationship between length of employment and the incidence of hypertension (p=0.048). In conclusion, length of employment is a factor associated with the incidence of hypertension among informal sector workers. Therefore, preventive efforts are needed through proper work time management, increasing workers’ awareness to routinely check blood pressure, and adopting healthy lifestyle behaviors to reduce the risk of hypertension. Keywords: hypertension, informal sector workers, risk factors, length of employment